Problematics of Mudharabah Financing at PT BPRS Aman Syariah Lampung - Dian Puspitasari (Jurnal Internasional Ekonomi Islam, 2022)
This article describes how the problems faced by management in the implementation of mudharabah financing at BPRS Aman Syariah Lampung. The research method used is a qualitative research method in which the primary data is obtained from the results of interviews conducted with the leadership and stakeholders of Islamic banks. And then the data will be analyzed using content analysis. The results of this study indicate that there are several problems faced by Islamic bank management when deciding to apply mudharabah financing. Mudharabah is the only contract that uses the principle of profit sharing. However, this problem arises when the fact is that this financing is not very attractive to customers. Ideally, profit sharing is a mechanism that dominates products in Islamic banks. But in reality, the profit sharing mechanism does not show a high enough percentage, it even tends to be low. The cause is the high level of risk in mudharabah financing. From the customer side, there are customers with moral hazard, lack of transparency when providing financial reports to the bank. This results in the amount of profit sharing distributed which tends to be flat and not in accordance with the portion it should be. This happens because of the low level of honesty on the part of the customer so that it damages the mudharabah financing contract from both parties.